Aplikasi Pengolahan Data Berbasis Web Menggunakan Framework Codeigniter - Aunul Farickin (JICTE (Journal of Information and Computer Technology Education), 2017)
Bengkel Sahabat was established in January 2005, in Sidoarjo with the previous name of "Bengkel Sahabat" serving magic turret, body repair, chassis repair, collision car repair, and painting. The process of improvement is the same as the other magic ketok that is synonymous with the culture of workmanship that is done in a closed, and in improving service "Bengkel Sahabat" has been equipped with facilities paint oven room, paint equipment, polish, or other equipment equivalent to workshop equipment body repair in general.CodeIgniter is an open source web application framework used to build dynamic php applications. The main purpose of Codeigniter development is to help developers to work on applications faster than writing all the code from scratch. Codeigniter provides a variety of libraries that can simplify the developmentThe results of this research produced a web-based data processing application on body repair shops and car paint three brothers to facilitate the users in running applications.